Strategi Komunikasi Pemasaran Produk Kosmetik Cream Zarita Untuk Meningkatkan Penjualan Melalui Akun Shopee Panji Apandi Shop - Diah Putri Annisa; Akhmad Syafrudin Syahri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The goal of this study is to increase sales of Cream Zarita cosmetic products by using Panji Apandi's Shopee shop account as a marketing communication strategy. The goal of this study is to determine how the marketing communication strategy used by Panji Apandi Shop affects Cream Zarita sales. This study employs several informants and a qualitative descriptive methodology. Information gathered via interviews, documentation, and direct observation at the study site served as the data source. Documentation, interviews, and observation are the methods used to acquire data. Techniques for analysing data include data reduction, data visualisation, and conclusion drawing. The results showed that Panji Apandi Shop uses marketing communication strategies to increase sales by live streaming, posting attractive product images and descriptions, and actively responding to consumer conversations, activating the free shipping feature, participating in shopee programs and events, and giving gifts to consumers. In the marketing activities carried out by Panji Apandi shop, it provides conclusions and results from the activities carried out there. Based on the research results, the marketing communication strategy model includes the application of the 4P marketing communication mix, namely product, price, place, promotion, combined with various marketing communication instruments.